Contango and Backwardation in Arbitrage-Free Futures-Markets - Hans Rau-Bredow (ZBW - Leibniz Information Centre for Economics, 2022)
This paper gives a short recapitulation of the constraints for forward and futures prices under the condition that no risk-free profits can be achieved through arbitrage activities.
Keywords: G13; 330; Contango; No-Arbitrage; Backwardation; Forwards and Futures